The dynamics of demotivation and remotivation among Korean high school EFL students. (April 2017) - Song, Bongsun; Kim, Tae-Young
Abstract: This study investigated factors influencing the demotivation and remotivation of Korean high school EFL students. Sixty-four grade 11 students were asked to draw a graph mapping their changes in English learning motivation from kindergarten to high school. From these, the data of 15 students who showed a decline in motivation and 13 students who showed a decline followed by an increase in motivation were chosen for further participation. These participants were asked to state the reasons for their motivational changes in response to an open-ended questionnaire, after which follow-up interviews were conducted. The results revealed that the majority of the participants became most demotivated in junior high school, mainly due to external factors, such as ineffective teaching methods, learning difficulty, and social pressure. However, 13 learners also experienced noticeable remotivation due to both external and internal factors. Major external remotivation factors included changes in study methods and inspiration from classmates, whereas the main internal factors were increased awareness of the necessity of English for the future, experiences of success, and interest in English culture. Based on these findings, pedagogical implications are provided.